Validity and practicality of project-based learning teaching modules to train life skills Era Society 5.0 (bioentrepreneurship) - Firdatus Sukma Fitri Shiyamsyah; Y. Yuliani; Yuni Sri Rahayu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
In the 21st century, Indonesian education must generate life skills for dealing with the era of society 5.0. Bioentrepreneurship skills are one of those needed to achieve the primary goal of society 5.0. However, teaching modules that combine entrepreneurship skills still need to be improved. This research aims to produce project-based learning teaching modules on plant growth and development material to train valid and practical society 5.0 (bioentrepreneurship) era skills. This research used a 4D. The teaching module's validity was determined by the validation results of three experienced lecturers. The practicality of the teaching module was measured based on the results of the readability test. The results of the teaching module validity test obtained an average score of 3.8, which is very valid. The results of the practicality test are reviewed from the textbook readability test, which is categorized as level 12 with a practical category. The results showed that project-based learning teaching modules on plant growth and development material are valid and practical to train the skills of the era of society 5.0 (bioentrepreneurship). Society era 5.0 (bioentrepreneurship) skills students can be trained by integrating plant growth and development biology material with microgreens cultivation project activities in project-based learning modules.